2013
DOI: 10.1002/dev.21154
|View full text |Cite
|
Sign up to set email alerts
|

Differences in placentophagia in relation to reproductive status in the california mouse (Peromyscus californicus)

Abstract: Parturient females ingest placenta in most mammalian species, whereas fathers may do so in species in which both parents provide care for their offspring. To determine if the propensity to eat placenta varies with reproductive status in the biparental California mouse, we presented placenta to virgin (housed with a same-sex pairmate), expectant (pregnant with their first litter), and multiparous adult males and females. Liver was presented identically, 3–7 days later, as a control. Multiparous females were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Specifically, females' response to placenta changes from aversion when they are sexually inexperienced to attraction during late pregnancy or with birthing experience [18,20]. This behavioral transition has been reported in rats (Rattus norvegicus; [18]), house mice (Mus musculus; [18]), California mice (Peromyscus californicus; [27]), Siberian hamsters (Phodopus sungorus; [9]), Djungarian hamsters (P. campbelli; [8,9]), rabbits (Oryctolagus cuniculus L.; [25]), and sheep (Ovis aries) [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, females' response to placenta changes from aversion when they are sexually inexperienced to attraction during late pregnancy or with birthing experience [18,20]. This behavioral transition has been reported in rats (Rattus norvegicus; [18]), house mice (Mus musculus; [18]), California mice (Peromyscus californicus; [27]), Siberian hamsters (Phodopus sungorus; [9]), Djungarian hamsters (P. campbelli; [8,9]), rabbits (Oryctolagus cuniculus L.; [25]), and sheep (Ovis aries) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies in the Djungarian hamster and the California mouse show that, similar to females, males may respond differently to placenta depending on their reproductive condition. In these two species, males are significantly less likely to ingest placenta when sexually inexperienced than when their mate is pregnant [9,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because placentophagia is so broadly displayed it is often suggested that it provides benefits to mothers and infants, which may include replenishing nutrients mothers lost during parturition, enhancing maternal attraction to newborns to promote their earliest physical contact, potentiating the opioid signaling underlying peripartum analgesia and the emergence of caregiving behaviors, assisting neonatal breathing by removing suffocating membranes, and perhaps diminishing predator attraction to the bloodied nest site (Kristal et al, ). Whereas adult female mammals are tremendously attracted to placenta and amniotic fluid immediately before, during, and after parturition, many or most nulliparous adult animals are thought to find afterbirth repugnant (Engwall & Kristal, ; Kristal & Graber, ; Kristal & Williams, ; Lévy, Poindroin, & Le Neindre ; Melo & González‐Mariscal, ; Perea‐Rodriguez & Saltzman, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the socially monogamous and biparental Djungarian hamster, Phodopus campbelli , sires readily consume placenta and amniotic fluid in addition to physically assisting the dam in the delivery of their offspring (Jones & Wynne‐Edwards, ). Monogamous California mouse ( Peromyscus californicus ) fathers also eat placenta while their mates give birth (Lee & Brown, ; also Perea‐Rodriguez & Saltzman, ). Furthermore, weanling‐aged male and female P. campbelli (average age of 24 days old) that had not been removed from their natal nest were observed to ingest placenta and amniotic fluid while their mothers gave birth to a litter conceived during a postpartum estrus (Vella, Evans, Ng, & Wynne‐Edwards, ).…”
Section: Introductionmentioning
confidence: 99%